BEST PRACTICES AND PITFALLS IN THE MEASUREMENTS OF THE CATALYTIC ACTIVITY OF MATERIALS IN THERMO-CATALYSIS - Martins, Leandro [UNESP]; Silva, Laura L. [UNESP]; Possato, Luiz G. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2024)
As catalysis grows as a multidisciplinary research area, many questions arise regarding the procedures used to determine the activity of materials in different chemical reactions. To correct inconsistencies, whether in definitions, concepts, or experimental methods, some catalysis science journals have been publishing editorials warning less-aware authors. In this work, we present some common concepts and procedures in thermo-catalysis, reviewing good practices and pointing out frequent failures that make it difficult to reliably compare the activity between materials of the same family and results from the scientific literature.
BOAS PRÁTICAS E EQUÍVOCOS NAS MEDIDAS DE ATIVIDADE CATALÍTICA DE MATERIAIS EM TERMOCATÁLISE
Keywords: carbon balance; conversion; distribution of products; leaching; selectivity